Impact of anti-inflammatory diets on cardiovascular disease risk factors: a systematic review and meta-analysis - Jiang, Ruixue; Wang, Ting; Han, Kunlin; Peng, Peiqiang; Zhang, Gaoning; Wang, Hanyu; Zhao, Lijing; Liang, Hang; Lv, Xuejiao; Du, Yanwei (Frontiers in Nutrition, 2025)
IntroductionChronic inflammation, via multiple pathways, influences blood pressure and lipid profiles, serving as a significant risk factor for the onset of cardiovascular disease (CVD). Anti-inflammatory dietary patterns may ameliorate CVD risk factors through the modulation of inflammatory mediators and metabolic factors, potentially leading to improved cardiovascular outcomes. Current findings regarding the relationship between dietary habits and CVD risk factors, such as blood pressure and lipid levels, exhibit considerable variability. We performed a comprehensive systematic review and meta-analysis to explore the possible association between anti-inflammatory dietary patterns (such as the Mediterranean diet, DASH diet, Nordic diet, Ketogenic diet, and Vegetarian diet) and CVD risk factors.MethodsWe conducted a comprehensive search across five databases: PubMed, Web of Science, Cochrane Library, Embase, and China National Knowledge Infrastructure (CNKI). Ultimately, we identified 18 eligible randomized controlled trials (including randomized crossover trials), which were subjected to meta-analysis utilizing RevMan 5 and Stata 18.ResultsA comprehensive meta-analysis of these studies conducted based on random effects model indicated that, in comparison to an Omnivorous diet, interventions centered on anti-inflammatory diets were linked to significant reductions in Systolic Blood Pressure (SBP) (MD: −3.99, 95% CI: −6.01 to −1.97; p = 0.0001), Diastolic Blood Pressure (DBP) (MD: −1.81, 95% CI: −2.73 to −0.88; p = 0.0001), Low Density Lipoprotein Cholesterol (LDL-C) (SMD: −0.23, 95% CI: −0.39 to −0.07; p = 0.004), Total Cholesterol (TC) (SMD: −0.31, 95% CI: −0.43 to −0.18; p < 0.00001) and High-sensitivity C-reactive Protein (hs-CRP) (SMD: −0.16, 95% CI: −0.31 to −0.00; p = 0.04). No notable correlations were identified between High Density Lipoprotein Cholesterol (HDL-C) and Triglycerides (TG).DiscussionThe findings indicate that anti-inflammatory diets may lower serum hs-CRP levels and positively influence the reduction of CVD risk factors, such as blood pressure and lipid profiles, thereby contributing to the prevention and progression of cardiovascular conditions. Most of the outcome indicators had low heterogeneity; sensitivity analyses were subsequently conducted on outcome measures demonstrating substantial heterogeneity, revealing that the findings remained consistent.